(untitled) (Communication & Society, 2009)
In spite of its stability in quantitative terms, the American romantic comedy of the new century shows certain decay as film genre, because of its incapacity to articulate a genuine romantic discourse, and of its recurrence to worn-out dramatic strategies. The increasing weight of coarseness in these romantic comedies is presented as the first new path in the necessary renewal of this genre.